2017
DOI: 10.1007/s11079-017-9472-x
|View full text |Cite
|
Sign up to set email alerts
|

Free Trade Agreements and Volatility of Stock Returns and Exchange Rates: Evidence from NAFTA

Abstract: 2This paper uses GARCH models and daily data to investigate the effect of the Canada -U.S. Free Trade Agreement (CUSFTA) and NAFTA on the volatility of, and the relationship between stock market returns and changes in bilateral exchange rates of the member countries. Empirical results indicate that the CUSFTA had a stabilizing effect on the Canadian and U.S. equity markets while increasing the volatility of the CAD/USD exchange rate. NAFTA further reduced the two stock markets' volatility, however unlike CUSFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
3
13
0
Order By: Relevance
“…In the North American Free Trade Agreement (NAFTA) region, Daelemans, et al [36] uniquely examined the effect of the free-trade agreement on the volatility of stock market returns and exchange rate fluctuations. The free-trade agreement had reduced the volatility of returns and increased the exchange rate fluctuations between the US and Canada.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the North American Free Trade Agreement (NAFTA) region, Daelemans, et al [36] uniquely examined the effect of the free-trade agreement on the volatility of stock market returns and exchange rate fluctuations. The free-trade agreement had reduced the volatility of returns and increased the exchange rate fluctuations between the US and Canada.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A number of international financial markets have been investigated in recent years by researchers These studies showed that there were a wide range of relationships between foreign stock markets (Nguyen & Lam, 2017). A global approach is being taken to these studies, as they concentrate on countries outside of trade blocs as well as those with trade blocs (Daelemans et al, 2018). Khan et al (2021), the literature offers benefits and problems associated with business integration (Paramati et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The paper proved that the basic determinants of Turkish stock returns are the changes in industrial production index, inflation rate, export, exchange rate, S&P's 500 index, world oil price index and the interest difference between Turkish Central Bank policy rate and the Federal Funds Rate of the USA in the long term. Daelemans et. al.…”
Section: Empirical Literature Surveymentioning
confidence: 99%
“…Trade agreements affect main variables such as exchange rates and stock prices between member countries through the real sector. For example, advantages may arise from increased commercial opportunities and greater competition (Daelemans et. al.…”
Section: Theoretical Frameworkmentioning
confidence: 99%